Watching Hamlet's Mother: Exploring the Relationship between Hamlet and Gertrude with a Year 7 Class. Issue 4 (2nd October 2019) - Philp, Hannah
ABSTRACT: In this essay, I draw on the experience of reading Hamlet with a class of 11- and 12-Year-old boys in a London comprehensive school. I explore how a number of comments in my classroom reveal the complexities of my students' thinking about gender and sexuality in Hamlet . I look at how these thoughts are difficult for the students to fully express, and I argue that it is necessary to attend to the heteroglossic nature of the language used within the classroom.